Tracking Murine Gammaherpesvirus 68 Infection of Germinal Center B Cells In Vivo - Collins, Christopher M. (Public Library of Science, 2012)

(untitled)
Infection of mice with murine gammaherpesvirus 68 (MHV68) provides a tractable small animal model to study various aspects of persistent gammaherpesvirus infection. We have previously utilized a transgenic MHV68 that expresses enhanced yellow fluorescent protein (EYFP) to identify infected cells. While this recombinant MHV68 has been useful for identifying infected cell populations by flow cytometry, it has been suboptimal for identification of infected cells in tissue sections due to the high solubility of EYFP. Efficient detection of EYFP expressed from the MHV68 genome in tissue sections requires fixation of whole organs prior to sectioning, which frequently leads to over-fixation of some cellular antigens precluding their detection. To circumvent this issue, we describe the generation and characterization of a transgenic MHV68 harboring a fusion gene composed of the EYFP coding sequence fused to the histone H2B open reading frame. Because the H2bYFP fusion protein is tightly bound in nucleosomes in the nucleus it does not freely diffuse out of unfixed tissue sections, and thus eliminates the need for tissue fixation. We have used the MHV68-H2bYFP recombinant virus to assess the location and distribution of virus infected B cells in germinal centers during the peak of MHV68 latency in vivo. These analyses show that the physical location of distinct populations of infected germinal center B cells correlates well with their surface phenotype. Furthermore, analysis of the distribution of virus infection within germinal center B cell populations revealed that ca. 70% of MHV68 infected GC B cells are rapidly dividing centroblasts, while ca. 20% have a clear centrocyte phenotype. Finally, we have shown that marking of infected cells with MHV68-H2bYFP is extended long after the onset of latency – which should facilitate studies to track MHV68 latently infected cells at late times post-infection.